Oxidative damage to methyl-CpG sequences inhibits the binding of the methyl-CpG binding domain (MBD) of methyl-CpG binding protein 2 (MeCP2) - Valinluck, Victoria (Oxford University Press, 2004)
Cytosine methylation in CpG dinucleotides is believed to be important in gene regulation, and is generally associated with reduced levels of transcription. Methylation-mediated gene silencing involves a series of DNA–protein and protein–protein interactions that begins with the binding of methyl-CpG binding proteins (MBPs) followed by the recruitment of histone-modifying enzymes that together promote chromatin condensation and inactivation. It is widely known that alterations in methylation patterns, and associated gene activities, are often found in human tumors. However, the mechanisms by which methylation patterns are altered are not currently understood. In this paper, we investigate the impact of oxidative damage to a methyl-CpG site on MBP binding by the selective placement of 8-oxoguanine (8-oxoG) and 5-hydroxymethylcytosine (HmC) in a MBP recognition sequence. Duplexes containing these specific modifications were assayed for binding to the methyl-CpG binding domain (MBD) of one member of the MBP family, methyl-CpG binding protein 2 (MeCP2). Our results reveal that oxidation of either a single guanine to 8-oxoG or of a single 5mC to HmC, significantly inhibits binding of the MBD to the oligonucleotide duplex, reducing the binding affinity by at least an order of magnitude. Oxidative damage to DNA could therefore result in heritable, epigenetic changes in chromatin organization.